Technology-based Waste Management in Batik Production - Purwati, Astri Ayu; Suriyanti, Linda Hetri; Retnawati, Sri Fitria; Yusrizal, Yusrizal; Desnelita, Yenny (International Conference on Business Management and Accounting, 2024)
The environmental challenges faced by Batik Bujang and Batik Candafa, two Riau-based SMEs, stem primarily from the production process, which generates substantial wastewater containing harmful chemicals. The improper disposal of these by-products poses serious risks to water bodies and surrounding ecosystems. This research aims to design a waste management system using eco-friendly technologies capable of processing up to 40 liters of wastewater, thereby minimizing environmental harm. A mixed-method approach was adopted, combining quantitative analysis of waste volume and chemical composition with qualitative insights from SME owners. The findings indicate a significant reduction in chemical pollutants post-treatment, aligning with eco-sustainability goals. This study fills the research gap by providing a technological solution specifically tailored to the needs of small-scale batik producers, emphasizing sustainability and environmental responsibility.